GM1 oligosaccharide-mediated rescue in GBA-linked Parkinson’s disease via modulation of lysosomal and mitochondrial dysfunctions - Giulia Lunghi; Carola Pedroli; Ilaria Tagliabue; Dorina Dobi; Maria Grazia Ciampa; Laura Mauri; Laura Rouvière; Alexandre Henriques; Noelle Callizot; Sandro Sonnino; Elena Chiricozzi; Maria Fazzari (Glycoconjugate Journal, 2025)

GM1 structural requirements to mediate neuronal functions - Maria Fazzari; Giulia Lunghi; Erika Di Biase; Margherita Maggioni; Emma Veronica Carsana; Laura Cioccarelli; Laura Vigani; Nicoletta Loberto; Massimo Aureli; Laura Mauri; Maria Grazia Ciampa; Manuela Valsecchi; et al. (Glycoconjugate Journal, 2023)

Emotional and Spontaneous Locomotor Behaviors Related to cerebellar Daidzein-dependent TrkB Expression Changes in Obese Hamsters - Raffaella Alò; Gilda Fazzari; Merylin Zizza; Ennio Avolio; Anna Di Vito; Ilaria Olvito; Rosalinda Bruno; Marcello Canonaco; Rosa Maria Facciolo (The Cerebellum, 2022)
Current evidence supports the beneficial role of phytoestrogens in metabolic diseases, but their influences on spontaneous motor and anxiety behaviors plus neuroprotective effects have still not been completely elucidated. With the present study, neuro-behavioral activities were correlated to daidzein (DZ)-dependent expression changes of a high affinity catalytic receptor for several neurotrophins, and namely tropomyosin-related kinase B receptor (TrkB) in the cerebellar cortex of high-fat diet (HFD) hamsters ( Mesocricetus auratus ). Indeed, these changes appear to be tightly linked to altered plasma lipid profiles as shown by reduced low-density lipoproteins plus total cholesterol levels in DZ-treated obesity hamsters accounting for increased spontaneous locomotor together with diminished anxiety activities in novel cage (NCT) and light/dark box (LDT) tests. For this latter case, the anxiolytic-like hamsters spent more time in the light compartment, which was retained the aversive area of the LDT box. As for the evaluation of the neurotrophin receptor site, significantly elevated TrkB levels were also detected, for the first time, in the cerebellum of obese hamsters treated with DZ. In this condition, such a treatment widely led to an overall improvement of HFD-induced neurodegeneration damages, above all in the Purkinje and granular layers of the cerebellum. In this context, the notably active TrkB signaling events occurring in a DZ-dependent manner may turn out to be a key neuroprotective element capable of restoring normal emotional and spontaneously linked locomotor behaviors regulated by cerebellar cortical areas especially in obesity-related conditions.

Novel insights on GM1 and Parkinson's disease: A critical review - Maria Fazzari; Erika Di Biase; Giulia Lunghi; Laura Mauri; Elena Chiricozzi; Sandro Sonnino (Glycoconjugate Journal, 2022)
GM1 is a crucial component of neuronal membrane residing both in the soma and nerve terminals. As reported in Parkinson’s disease patients, the reduction of GM1 determines the failure of fundamental functional processes leading to cumulative cell distress up to neuron death. This review reports on the role of GM1 in the pathogenesis of the disease, illustrating the current data available but also hypotheses on the additional mechanisms in which GM1 could be involved and which require further study. In the manuscript we discuss these points trying to explain the role of diminished content of brain GM1, particularly in the nigro-striatal system, in Parkinson’s disease etiology and progression.

Daidzein Pro-cognitive Effects Coincided with Changes of Brain Neurotensin1 Receptor and Interleukin-10 Expression Levels in Obese Hamsters - Raffaella Alò; Gilda Fazzari; Merylin Zizza; Ennio Avolio; Anna Di Vito; Rosalinda Bruno; Giovanni Cuda; Tullio Barni; Marcello Canonaco; Rosa Maria Facciolo (Neurotoxicity Research, 2021)

Turning the spotlight on the oligosaccharide chain of GM1 ganglioside - Elena Chiricozzi; Erika Di Biase; Giulia Lunghi; Maria Fazzari; Nicoletta Loberto; Massimo Aureli; Laura Mauri; Sandro Sonnino (Glycoconjugate Journal, 2021)
It is well over a century that glycosphingolipids are matter of interest in different fields of research. The hydrophilic oligosaccharide and the lipid moiety, the ceramide, both or separately have been considered in different moments as the crucial portion of the molecule, responsible for the role played by the glycosphingolipids associated to the plasma-membranes or to any other subcellular fraction. Glycosphingolipids are a family of compounds characterized by thousands of structures differing in both the oligosaccharide and the ceramide moieties, but among them, the nervous system monosialylated glycosphingolipid GM1, belonging to the group of gangliosides, has gained particular attention by a multitude of Scientists. In recent years, a series of studies have been conducted on the functional roles played by the hydrophilic part of GM1, its oligosaccharide, that we have named “OligoGM1”. These studies allowed to shed new light on the mechanisms underlying the properties of GM1 defining the role of the OligoGM1 in determining precise interactions with membrane proteins instrumental for the neuronal functions, leaving to the ceramide the role of correctly positioning the GM1 in the membrane crucial for the oligosaccharide-protein interactions. In this review we aim to report the recent studies on the cascade of events modulated by OligoGM1, as the bioactive portion of GM1, to support neuronal differentiation and trophism together with preclinical studies on its potential to modify the progression of Parkinson’s disease.

Modulation of calcium signaling depends on the oligosaccharide of GM1 in Neuro2a mouse neuroblastoma cells - Giulia Lunghi; Maria Fazzari; Erika Di Biase; Laura Mauri; Sandro Sonnino; Elena Chiricozzi (Glycoconjugate Journal, 2020)
Recently, we demonstrated that the oligosaccharide portion of ganglioside GM1 is responsible, via direct interaction and activation of the TrkA pathway, for the ability of GM1 to promote neuritogenesis and to confer neuroprotection in Neuro2a mouse neuroblastoma cells. Recalling the knowledge that ganglioside GM1 modulates calcium channels activity, thus regulating the cytosolic calcium concentration necessary for neuronal functions, we investigated if the GM1-oligosaccharide would be able to overlap the GM1 properties in the regulation of calcium signaling, excluding a specific role played by the ceramide moiety inserted into the external layer of plasma membrane. We observed, by calcium imaging, that GM1-oligosaccharide administration to undifferentiated Neuro2a cells resulted in an increased calcium influx, which turned out to be mediated by the activation of TrkA receptor. The biochemical analysis demonstrated that PLCγ and PKC activation follows the TrkA stimulation by GM1-oligosaccharide, leading to the opening of calcium channels both on the plasma membrane and on intracellular storages, as confirmed by calcium imaging experiments performed with IP3 receptor inhibitor. Subsequently, we found that neurite elongation in Neuro2a cells was blocked by subtoxic administration of extracellular and intracellular calcium chelators, suggesting that the increase of intracellular calcium is responsible of GM1-oligosaccharide mediated differentiation. These results suggest that GM1-oligosaccharide is responsible for the regulation of calcium signaling and homeostasis at the base of the neuronal functions mediated by plasma membrane GM1.

The oligosaccharide portion of ganglioside GM1 regulates mitochondrial function in neuroblastoma cells - Maria Fazzari; Matteo Audano; Giulia Lunghi; Erika Di Biase; Nicoletta Loberto; Laura Mauri; Nico Mitro; Sandro Sonnino; Elena Chiricozzi (Glycoconjugate Journal, 2020)

Gangliosides in the differentiation process of primary neurons: the specific role of GM1-oligosaccharide - Erika Di Biase; Giulia Lunghi; Maria Fazzari; Margherita Maggioni; Diego Yuri Pomè; Manuela Valsecchi; Maura Samarani; Pamela Fato; Maria Grazia Ciampa; Simona Prioni; Laura Mauri; Sandro Sonnino; et al. (Glycoconjugate Journal, 2020)

The Neuroprotective Role of the GM1 Oligosaccharide, II3Neu5Ac-Gg4, in Neuroblastoma Cells - Elena Chiricozzi; Margherita Maggioni; Erika di Biase; Giulia Lunghi; Maria Fazzari; Nicoletta Loberto; Maffioli Elisa; Francesca Grassi Scalvini; Gabriella Tedeschi; Sandro Sonnino (Molecular Neurobiology, 2019)

Application of the Co-culture Membrane System Pointed to a Protective Role of Catestatin on Hippocampal Plus Hypothalamic Neurons Exposed to Oxygen and Glucose Deprivation - Maria Mele; Sabrina Morelli; Gilda Fazzari; Ennio Avolio; Raffaella Alò; Antonella Piscioneri; Loredana De Bartolo; Rosa Maria Facciolo; Marcello Canonaco (Molecular Neurobiology, 2017)

Unpredictable Chronic Mild Stress Paradigm Established Effects of Pro- and Anti-inflammatory Cytokine on Neurodegeneration-Linked Depressive States in Hamsters with Brain Endothelial Damages - Ennio Avolio; Gilda Fazzari; Maria Mele; Raffaella Alò; Merylin Zizza; Wei Jiao; Anna Di Vito; Tullio Barni; Maurizio Mandalà; Marcello Canonaco (Molecular Neurobiology, 2017)

Role of Leptin and Orexin-A Within the Suprachiasmatic Nucleus on Anxiety-Like Behaviors in Hamsters - Raffaella Alò; Ennio Avolio; Maria Mele; Gilda Fazzari; Antonio Carelli; Rosa Maria Facciolo; Marcello Canonaco (Molecular Neurobiology, 2017)

Distinct Amygdalar AMPAergic/GABAergic Mechanisms Promote Anxiolitic-Like Effects in an Unpredictable Stress Model of the Hamster - Raffaella Alò; Maria Mele; Ennio Avolio; Gilda Fazzari; Marcello Canonaco (Journal of Molecular Neuroscience, 2015)